PENGARUH METODE PEMBERIAN TUGAS DALAM PEMBELAJARAN PENDIDIKAN JASMANI, OLAHRAGA DAN KESEHATAN TERHADAP HASIL BELAJAR CHEST PASS BOLA BASKET (STUDI PADA SISWA KELAS XI SMA NEGERI 1 SOOKO) - PAMUNGKAS, ARGO (Jurnal Pendidikan Olahraga dan Kesehatan, 2014)
Abstract Learning method is one of key succses in teaching and learning activities. In teaching and learning process teachers should be more variable to determine the method of learning so students will not feel bored. Learning method chosen should be appropriate to the school and students skills for more effective learning process. One of methods that can be selected is the method of assignment. Assignment method is expected to stimulate the students to be more active in learning, more responsible, improve learning outcomes and sensitize students to always take advantage of free time for the things that support learning by filling in positive activities. This research is aimed to find out the influence assignment method in  physical education to the learning result of chest pass basketball. This research was experimental with quantitative descriptive approach. Subject in this  research were 52 students of 11th grade in Senior High School 1 Sooko using cluster random sampling. The class selected as the sample classes was XI IS 1 and XI IS 2 amounted of 26 students. Then divided into experimental group and control group. The instrument was test push pass for accuracy. From the calculation can be concluded that there was a significant effect of assignment method in the learning physical education to the learning result of chest pass basketball as evidenced by the results  2,3094 >  2,0105 with significance level 0,05. While the effect is found to be 17,63%. Keywords: Assignment method, learning result, chest pass basketball